Genetic susceptibility variants of vascular dementia among Asians: a systematic review and meta-analysis - Vasudevan, R.; Nur Afiqah, M.; Mohd Nazil, S.; Wan Aliaa, W.S.; Liyana Najwa, I.M.; Mohd Hazmi, M.; Siew Mooi, C.; Abdul Hanif Khan, Y.K.; Hamidon, B.; Pannerselvam, P.; Suganthi, V.; Narenkumar, J. (Karger Publishers, 2024)
Introduction: Vascular dementia (VaD), a neurocognitive impairment directly related to vascular injury, is the second most common cause of age-related dementia. Although numerous studies have investigated candidate genetic polymorphisms associated with VaD in Asia, the genetics of VaD remains unclear. Methods: This review provides an updated meta-analysis of genetic polymorphisms associated with VaD in Asians, using the PRISMA guidelines. Published literature up to May 2021 was extracted from the PubMed, Scopus, Ovid, and EBSCOhost databases. Meta-analysis was conducted using the Open Meta analyst, Review Manager, and MedCalc® Statistical Software. Trial sequential analysis (TSA) was performed using TSA viewer software. Results: A total of 46 eligible studies, comprising 23 genes and 35 single nucleotide polymorphisms, were retrieved. The meta-analysis was conducted on the following genetic polymorphisms, APOE ε2/3/4, MTHFR rs1801131, ACE rs4340 (I/D) gene polymorphism, and a PSEN1 intron 8 variant. The pooled odds ratio (ORs) revealed a significant increase in the risk of VaD in the apolipoprotein E (APOE) ε4 allelic model (OR, 1.79, p < 0.001), and the methylenetetrahydrofolate reductase (MTHFR) rs1801133 polymorphism T allele in the allelic model (OR, 1.23, p = 0.013). Conclusion: Our findings provide evidence that genetic polymorphisms of the APOE ε4 allele and MTHFR rs1801133 T allele increase the risk of developing VaD in Asians. However, future large-scale investigations examining particularly on South-Eastern and West-Asian populations are highly recommended.